Bridging Theory and Practice: Challenges and Opportunities in Dual Training for Sustainability Education at Spanish Universities - Susana Quirós-Alpera; Aloysius O. S. B. Roets; Rafael Robina-Ramírez; Ana Leal-Solís (Societies)
This study investigates the implementation of dual training at the University of Extremadura (2023–2024), aiming to bridge theoretical academic knowledge with practical industry insights. This research utilizes SmartPLS 4.1.0.9 SEM-PLS software to explore the relationship between corporate engagement, academic outcomes, and sustainability challenges, validating hypotheses and refining dual training models in sustainability education. Key variables include Information Collection (IG), Sustainable Business Challenges (SCh), and Knowledge Developed by Business Strategies (KBS). The findings reveal that while the dual training model successfully integrates academic curricula with corporate engagement, it struggles to connect business strategies with actionable recommendations and has limited impact on improving teaching methods. This study identifies structural and practical barriers in the Spanish education system that hinder the full realization of dual training’s potential. To address these challenges, this research recommends incorporating continuous feedback mechanisms throughout the learning process and enhancing mentorship opportunities. Continuous feedback would allow students to refine their conclusions, leading to more practical and sustainable solutions. Additionally, the use of authentic case studies and greater industry involvement would help students bridge the gap between theoretical knowledge and real-world applications, enabling them to generate actionable recommendations and better understand sustainability challenges and business strategies. These recommendations aim to improve student learning outcomes and strengthen the integration of academic and corporate practices, fostering more effective sustainability education.